(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article examines economic processes with correlational dependencies that change over time according to a harmonic law, and it also proposes a method for determining the period, phase, and frequency of the oscillations in these processes. The article proposes a method for determining the coefficients A and B in the harmonic function, which was obtained as a result of research.